CUTANEOUS LARVA MIGRANS - A TYPICAL CASE REPORT - Santos, Guida; João, Alexandre (Journal of the Portuguese Society of Dermatology and Venereology, 2013)
Cutaneous larva migrans is common in tropical and sub-tropical countries and is caused by the migration of nematode ́s larvae in the skin. The diagnosis is made primarily with the epidemiological characteristics of the derma- tosis and its clinical semiology. Usually the treatment is successful with albendazole or ivermectin. We describe the case of a 54-year-old woman returned from holidays in Jamaica 15 days ago. The patient had on site, a well delimited, 2mm wide erythematous papule on the external face of the left foot, progressing along the plant throu- gh a serpiginosum track until reaching the internal face of the foot. She denied fever or other symptoms. Clinically the dermatosis was very suggestive of cutaneous larva migrans and the patient was treated with albendazole. This case serves to remind an uncommon dermatosis in Portugal. It also intends to alert to the early recognition of this skin infestation. Although self-limiting, this disease is cause of great anxiety for the patients. KEYWORDS – Larva migrans; Skin diseases.